A study of doctoral time-to-degree in selected disciplines at South African public universities - van Lill, M. H. (South African Journal of Higher Education, 2024)
Scholarship on doctoral success highlights differences in timely degree attainment between disciplines. However, research on doctoral education in South Africa is limited to identifying general factors that affect the successful completion of a doctoral degree with very little reference to differences across disciplines. This study’s objective is to compare time-to-degree, as the number of years between a doctoral student’s commencement year and graduation year, across selected disciplines as well as to identify factors, above and beyond that of disciplinary field, which are explanatory of shorter time-to-degree. The study investigates the role of selected student demographics (such as commencement age, gender, race, and nationality), institutional (type of higher education institution), and situational factors (such as part-time or full-time enrolment) in predicting doctoral time-to-degree. Results of multiple linear regression models indicate that mode of enrolment is the strongest predictor of completion time with part-time students recording a statistically significantly longer time-to-degree when compared to full-time students. A student’s discipline, nationality, and institution are also identified as statistically significant predictors of time-to-degree while gender, race, and age are not. However, the interaction between commencement age and enrolment mode is indicated to be a strong predictor of doctoral completion time. Although shorter completion times can be considered an indicator of efficiency at doctoral level, it is imperative to consider wider contextual factors in thinking about this issue.